1995
DOI: 10.1007/bf01271541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pergolide on endogenous and exogenous L-DOPA metabolism in the rat striatum: a microdialysis study

Abstract: We used a model of intrastriatal microdialysis in freely moving rats to study the effect of pergolide, a mixed D1/D2 dopamine (DA) receptor agonist with predominant D2 action in vivo, on the biotransformation of endogenous and exogenous L-DOPA. Levels of L-DOPA, DA, DOPAC, HVA and 5-HIAA were measured by high performance liquid chromatography. Pergolide (50 micrograms/kg, i.p.) caused a 47%, 65% and 70% decrease in basal striatal extracellular (EC) levels of DOPAC, HVA and DA, respectively. L-DOPA (100 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In previous reports, it has been demonstrated that pergolide inhibits endogenous DA release and exogenous L-dopa metabolism. 43 These observations suggest possibilities that pergolide increases endogenous dopamine level, and consequently quinoprotein formation is slightly increased after the L-dopa + pergolide treatment in our experiments.…”
Section: Discussionmentioning
confidence: 87%
“…In previous reports, it has been demonstrated that pergolide inhibits endogenous DA release and exogenous L-dopa metabolism. 43 These observations suggest possibilities that pergolide increases endogenous dopamine level, and consequently quinoprotein formation is slightly increased after the L-dopa + pergolide treatment in our experiments.…”
Section: Discussionmentioning
confidence: 87%
“…2 ). No effects of dopamine agonists were found on the levels of the metabolite 5-HIAA ( 35 , 124 ). Additionally, it was suggested that D 2 receptor agonists modulate serotonin afferents presynaptically in the hippocampus ( 125 ) or the SN ( 126 ).…”
Section: Dopaminergic Treatment Effects On Endogenous Metabolites Levmentioning
confidence: 99%